Characteristics of highly mentioned academic papers in the news - Nabavi, Majid (Malaysian Journal of Library and Information Science, 2023)
The primary objective of this paper was to provide insights into papers that garnered significant attention in news outlets. A sample of seventy academic papers, each with over 500 mentions in news outlets, was chosen for this study via Dimensions. Comprehensive data for each paper was extracted from diverse sources, encompassing the Journal Citation Report (JCR), Scopus, SCImago, Altmetric.com, as well as analyses of the titles and abstracts. Findings concerning the characteristics of these papers revealed that those highly referenced in news outlets tend to be predominantly published in open access within prestigious specialized journals, with a primary focus on medical and health-related topics. The majority of these papers have been published within the last three years, with each accumulating more than 100 citations in Scopus. Additionally, the results indicated that the number of authors and international collaboration does not exert a substantial influence on the frequency of news posts dedicated to highly mentioned papers in news outlets. However, the journal’s impact factor, paper citation count, and the alignment of the paper’s affiliation country with that of the news outlets displayed a notable correlation with the frequency of news posts pertaining to these papers. Based on the study’s findings, it can be inferred that science journalists place higher emphasis on considerations such as proximity, prestige, timeliness, and relevance in their coverage, prioritizing these factors over other news values.